2009
DOI: 10.1083/jcb.200811099
|View full text |Cite
|
Sign up to set email alerts
|

Formation of cristae and crista junctions in mitochondria depends on antagonism between Fcj1 and Su e/g

Abstract: Crista junctions (CJs) are important for mitochondrial organization and function, but the molecular basis of their formation and architecture is obscure. We have identified and characterized a mitochondrial membrane protein in yeast, Fcj1 (formation of CJ protein 1), which is specifically enriched in CJs. Cells lacking Fcj1 lack CJs, exhibit concentric stacks of inner membrane in the mitochondrial matrix, and show increased levels of F1FO–ATP synthase (F1FO) supercomplexes. Overexpression of Fcj1 leads to incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

39
460
1
13

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 282 publications
(516 citation statements)
references
References 65 publications
(103 reference statements)
39
460
1
13
Order By: Relevance
“…In addition, stacked IMM disconnected from the IBMs were observed in the liver mitochondria of our patient -a characteristic phenotype similar to that observed in yeast and human cells lacking MICOS function. [4][5][6]8,[11][12][13] The cause of deterioration in our patients could be the mitochondrial respiratory chain dysfunction, which mainly affected the central nervous system, the liver and the heart. The respiratory growth defect observed in yeast strains lacking MICOS has been attributed to impaired organization and/or position of the respiratory complex III and IV.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, stacked IMM disconnected from the IBMs were observed in the liver mitochondria of our patient -a characteristic phenotype similar to that observed in yeast and human cells lacking MICOS function. [4][5][6]8,[11][12][13] The cause of deterioration in our patients could be the mitochondrial respiratory chain dysfunction, which mainly affected the central nervous system, the liver and the heart. The respiratory growth defect observed in yeast strains lacking MICOS has been attributed to impaired organization and/or position of the respiratory complex III and IV.…”
Section: Discussionmentioning
confidence: 99%
“…Yeast strains W303, BY4742, Δe in W303, Δe in BY4742, Δg in W303, Δg in BY4742, Δk in W303 and 4ΔTM1 in D273-10B [EUROSCAF, (3,16)] were grown under nonfermentable conditions as described (43). Mitochondria were isolated by enzymatic digestion of the cell wall, followed by differential centrifugation as described (44).…”
Section: Methodsmentioning
confidence: 99%
“…These data indicated that anchoring of mitofilin to the outer membrane is not sufficient for crista junction formation and that the role of mitofilin for crista junction formation likely involves further proteins. Indeed, earlier work had already suggested that mitofilin proteins are part of very large protein complexes, but the molecular composition of these structures had remained enigmatic (John et al , 2005 ;Rabl et al , 2009 ;Mun et al , 2010 ).…”
Section: Structural and Functional Links Of Crista Junctions And Membmentioning
confidence: 99%
“…The Saccharomyces cerevisiae mitofilin protein (also termed formation of crista junctions 1/Fcj1) was the first protein shown to be mainly located at crista junctions Harner et al , 2011 ). Depletion of mitofilin in human cells and worms or deletion of mitofilin in yeast leads to an extension of the inner membrane surface, a massive loss of crista junctions and to abnormal crista structures that appear as stacked lamellae disconnected from the inner boundary membrane (John et al , 2005 ;Rabl et al , 2009 ;Mun et al , 2010 ;Harner et al , 2011 ;Hoppins et al , 2011 ;von der Malsburg et al , 2011 ;Alkhaja et al , 2012 ). These observations point to a conserved function of mitofilin in the formation and/or maintenance of crista junctions.…”
mentioning
confidence: 99%